Evaluation of the Impact of the Introduction of EN Iso 9001: 2015 in an Engineering Company - Šuman, Nataša; Hozjan, Stanislav (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Quality assurance is key to delivering services in the construction process, most of which are provided by engineering companies. Factors that affect quality assurance in construction services include inadequate specifications in tenders, incomplete or poor input data, inadequate communication between participants, inadequate quality control, etc. In order to achieve a high level of quality, it is important to establish a quality management system. The aim of this article is to present the basic concept for the introduction of a quality management and quality assurance system in engineering companies in accordance with the requirements of the EN ISO 9001:2015 standard. By analyzing and considering the characteristics of the company ZEU d. o. o., an assessment of the impact on the company's operations and business is made. The main findings are that the introduction of a quality system leads to the introduction of structured processes, better control of projects, a reduction in errors, improved efficiency and productivity, increased customer confidence and, last but not least, a higher reputation of the company.